Tumor microenvironment-responsive artesunate loaded Z-scheme heterostructures for synergistic photo-chemodynamic therapy of hypoxic tumor - Jie Lv; Xiaoyu Wang; Xue Zhang; Runpei Xu; Shuyang Hu; Shuangling Wang; Meng Li (Elsevier, 2023)
Tumor microenvironment (TME) with the particular features of severe hypoxia, insufficient endogenous H2O2, and overexpression of glutathione (GSH) markedly reduced the antitumor efficacy of monotherapy. Herein, a TME-responsive multifunctional nanoplatform (Bi2S3@Bi@PDA-HA/Art NRs) was presented for synergistic photothermal therapy (PTT), chemodynamic therapy (CDT), and photodynamic therapy (PDT) to achieve better therapeutic outcomes. The Z-scheme heterostructured bismuth sulfide@bismuth nanorods (Bi2S3@Bi NRs) guaranteed excellent photothermal performance of the nanoplatform. Moreover, its ability to produce O2 and reactive oxygen species (ROS) synchronously could relieve tumor hypoxia and improve PDT outcomes. The densely coated polydopamine/ammonium bicarbonate (PDA/ABC) and hyaluronic acid (HA) layers on the surface of the nanoplatform enhanced the cancer-targeting capacity and induced the acidic TME-triggered in situ "bomb-like" release of Art. The CDT treatment was achieved by activating the released Art through intracellular Fe2+ ions in an H2O2-independent manner. Furthermore, decreasing the glutathione peroxidase 4 (GPX4) levels by Art could also increase the PDT efficiency of Bi2S3@Bi NRs. Owing to the synergistic effect, this nanoplatform displayed improved antitumor efficacy with minimal toxicity both in vitro and in vivo. Our design sheds light on the application of phototherapy combined with the traditional Chinese medicine monomer-artesunate in treating the hypoxic tumor.